2006
DOI: 10.1002/nbm.1088
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of gadolinium‐labeled pancreatic islets for experimental transplantation

Abstract: New imaging techniques that couple anatomical resolution to sensitivity may greatly contribute to improving islet transplantation. In the present work, a report is given of the direct detection of islets by magnetic resonance imaging (MRI) after ex vivo cell labeling with the MRI T(1) contrast agent GdHPDO3A. Experiments on mouse and human islets demonstrated well-tolerated uptake of GdHPDO3A, based on morphology, viability, glucose-dependent insulin response and apoptosis/toxicity gene array profile. GdHPDO3A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 23 publications
3
74
0
Order By: Relevance
“…MR contrast media have been successfully used in labeling cells to monitor in situ cell retention, engraftment and migration (41)(42)(43). Superparamagnetic iron oxide (SPIO) and gadolinium chelates (44,45) are used for cell labeling. In a preliminary study, investigators found that Feridex 1 inhibited chondrocyte differentiation in treated stem cells (46).…”
Section: Mr Contrast Media and Cells Labelingmentioning
confidence: 99%
“…MR contrast media have been successfully used in labeling cells to monitor in situ cell retention, engraftment and migration (41)(42)(43). Superparamagnetic iron oxide (SPIO) and gadolinium chelates (44,45) are used for cell labeling. In a preliminary study, investigators found that Feridex 1 inhibited chondrocyte differentiation in treated stem cells (46).…”
Section: Mr Contrast Media and Cells Labelingmentioning
confidence: 99%
“…[32] PIs efficiently accumulate even low-molecular-weight Gd-based CAs with a low efflux; [31] nevertheless, as PIs consists of several types of cells and only an MRI-active CA was used in this case, it was not possible to precisely localize the CA inside the islets. For this reason, we chose the new dual CA for the labelling of PIs.…”
Section: Labelling Of Pancreatic Isletsmentioning
confidence: 96%
“…Transplanted islets have been labeled with superparamagnetic iron oxide (SPIO) nanoparticles [67][68][69][70] or paramagnetic gadolinium based agents for negative (hypointense) and positive (hyperintense) [71] contrast 1H MRI, respectively. In addition, transplanted islets have been monitored with 19F MRI in animal models [72,73].…”
Section: Mri Tracking Of Transplanted Isletsmentioning
confidence: 99%